2023
DOI: 10.7759/cureus.42981
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Trends and Factors Associated With the Morbidity Rate of Gonorrhea: A CDC-WONDER Database Analysis

Micheal K Akinboro,
John Mmaduabuchi,
Papa Kwame Antwi Beeko
et al.

Abstract: Background and objective: Gonorrhea is a prevalent sexually transmitted illness caused by the bacteria Neisseria gonorrhoeae, leading to serious health consequences such as pelvic inflammatory disease (PID), infertility, ectopic pregnancy, and increased susceptibility to HIV infection. Despite advancements in prevention and treatment, gonorrhea remains a significant public health problem in the United States (US) due to its widespread incidence, potential consequences, and the growth of antibiotic resistance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…A study on testicular cancer incidence by Gold et al found that younger (<45), Hispanic, or black men were more likely to die in medical facilities [11]. Moreover, a study by Akinboro et al, on the epidemiological trends associated with the morbidity rate of gonorrhea, found that the morbidity was the highest in the age groups between the ages of 19-24 [12].…”
Section: Discussionmentioning
confidence: 99%
“…A study on testicular cancer incidence by Gold et al found that younger (<45), Hispanic, or black men were more likely to die in medical facilities [11]. Moreover, a study by Akinboro et al, on the epidemiological trends associated with the morbidity rate of gonorrhea, found that the morbidity was the highest in the age groups between the ages of 19-24 [12].…”
Section: Discussionmentioning
confidence: 99%